Asymmetric response properties of rapidly adapting mechanoreceptive fibers in the rat glabrous skin. (March 2013) - Devecıoğlu, İsmaıl and Güçlü, Burak
<x xml:space="preserve">Abstract</x> Previous histological and neurophysiological studies have shown that the innervation density of rapidly adapting (RA) mechanoreceptive fibers increases towards the fingertip. Since the psychophysical detection threshold depends on the contribution of several RA fibers, a high innervation density would imply lower thresholds. However, our previous human study showed that psychophysical detection thresholds for the Non-Pacinian I channel mediated by RA fibers do not improve towards the fingertip. By recording single-unit spike activity from rat RA fibers, here we tested the hypothesis that the responsiveness of RA fibers is asymmetric in the proximo-distal axis which may counterbalance the effects of innervation density. RA fibers (n = 32) innervating the digital glabrous skin of rat hind paw were stimulated with 40-Hz sinusoidal mechanical bursts at five different stimulus locations relative to the receptive field (RF) center (two distal, one RF center, two proximal). Different contactor sizes (area: 0.39, 1.63, 2.96 mm2) were used. Rate-intensity functions were constructed based on average firing rates, and the absolute spike threshold and the entrainment threshold were obtained for each RA fiber. Thresholds for proximal stimulus locations were found to be significantly higher than those for distal stimulus locations, which suggests that the mechanical stimulus is transmitted better towards the proximal direction. The effect of contactor size was not significant. Mechanical impedance of the rat digital glabrous skin was further measured and a lumped-parameter model was proposed to interpret the relationship between the asymmetric response properties of RA fibers and the mechanical properties of the skin.